Nonlinear Smoothing and Multiresolution Analysis - Rohwer, Carl.; SpringerLink (Online service) (Basel : Birkhäuser Basel, 2005)
This monograph presents a new theory for analysis, comparison and design of nonlinear smoothers, linking to established practices. Although a part of mathematical morphology, the special properties yield many simple, powerful and illuminating results leading to a novel nonlinear multiresolution analysis with pulses that may be as natural to vision as wavelet analysis is to acoustics. Similar to median transforms, they have the advantages of a supporting theory, computational simplicity, remarkable consistency, full trend preservation, and a Parceval-type identity. Although the perspective is new and unfamiliar to most, the reader can verify all the ideas and results with simple simulations on a computer at each stage. The framework developed turns out to be a part of mathematical morphology, but the additional specific structures and properties yield a heuristic understanding that is easy to absorb for practitioners in the fields like signal- and image processing. The book targets mathematicians, scientists and engineers with interest in concepts like trend, pulse, smoothness and resolution in sequences.
Operators on Sequences -- Basic Rank Selectors, Pulses and Impulses -- LULU-Smoothers, Signals and Ambiguity -- LULU-Intervals, Noise and Co-idempotence -- Smoothing and Approximation with Signals -- Variation Reduction and Shape Preservation -- Multiresolution Analysis of Sequences -- The Discrete Pulse Transform -- Fair Comparison with Linear Smoothers -- Interpretation and Future.
Keywords: Mathematics; Approximation theory; Fourier analysis; Operator theory; Applied mathematics; Engineering mathematics; Mathematics; Mathematics, general; Approximations and Expansions; Fourier Analysis; Operator Theory; Appl.Mathematics/Computational Methods of Engineering; Signal, Image and Speech Processing; Electronic books